Knowledge About Dental Caries Using Media High-Five Pictures (Third Grade Students of SDN 2 Serut Tulungagung) - Balady, Vazabina Najmal; Putri, I Gusti Ayu Kusuma Astuti Ngurah; Prasetyowati, Silvia (SURABAYA DENTAL THERAPIST JOURNAL, 2026)
Dental caries is one of the most common dental health problems in children, especially in Indonesia. The incidence of dental caries is widely experienced by both children and adults. Dental caries can occur due to several factors, one of which is the lack of knowledge about dental caries. The problem found by researchers is the high rate of dental caries in third grade students of SDN 2 Serut Tulungagung. This study aims to determine knowledge about dental caries by using media high-five pictures on third grade students of SDN 2 Serut Tulungagung. The type of research used is descriptive with 36 students as respondents. Data collection instruments using questionnaires, data analysis techniques by calculating the average answer to the questionnaire. The results showed that knowledge about dental caries in third grade students of SDN 2 Serut Tulungagung was in the good category. The conclusion of this study is that the average knowledge about the meaning of dental caries, the causes of dental caries, how to prevent dental caries, the impact of dental caries, and how to treat dental caries is in the good category.